Humans as a service: the promise and perils of work in the gig economy - Prassl, Jeremias (Oxford, 2018)
"What if your boss was an algorithm? The gig economy promises to revolutionise work as we know it, offering flexibility and independence instead of 9-to-5 drudgery. The potential benefits are enormous: consumers enjoy the convenience and affordability of on-demand work while micro-entrepreneurs turn to online platforms in search of their next gig, task, or ride. Is this the future of work? This book offers an engaging account of work in the gig economy across the world. Competing narratives abound: on-demand gigs offer entrepreneurial flexibility - or precarious work, strictly controlled by user ratings and algorithmic surveillance. Platforms' sophisticated technology is the product of disruptive innovation - whilst the underlying business model has existed for centuries. How can we protect consumers & workers without stifling innovation? As courts and governments around the world begin to grapple with the gig economy, Humans as a Service explores the challenges of on-demand work, and explains how we can ensure decent working conditions, protect consumers, and foster innovation. Employment law plays a central role in levelling the playing field: gigs, tasks, and rides are work â and should be regulated as such."